2017
DOI: 10.1159/000479745
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration for the Diagnosis of Isolated Mediastinal and Hilar Lymphadenopathy

Abstract: Background: Although many studies have assessed the diagnostic utility of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in the context of a specific disease, few studies have assessed the overall diagnostic yield, sensitivity, and negative predictive value in patients with isolated mediastinal and hilar lymphadenopathy (IMHL). Objective: We evaluated the performance of EBUS-TBNA for diagnosing IMHL in a population with a high prevalence of concurrent or preexisting non-pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Previously samples such as pleural fluids, bronchoscopic brushes, and CT fine-needle aspiration (FNA) samples were more common and were evaluated for molecular testing by single-gene approaches [2]. Mediastinal and hilar nodes can be easily sampled using EBUS-TBNA with few side effects and a 95% sensitivity for diagnosing malignancy [5, 7-9]. The EBUS-TBNA procedure can be accompanied by rapid on-site evaluation (ROSE) of sample material, using air-dried and Diff-Quik-stained cytology smears to provide immediate feedback for the proceduralist [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Previously samples such as pleural fluids, bronchoscopic brushes, and CT fine-needle aspiration (FNA) samples were more common and were evaluated for molecular testing by single-gene approaches [2]. Mediastinal and hilar nodes can be easily sampled using EBUS-TBNA with few side effects and a 95% sensitivity for diagnosing malignancy [5, 7-9]. The EBUS-TBNA procedure can be accompanied by rapid on-site evaluation (ROSE) of sample material, using air-dried and Diff-Quik-stained cytology smears to provide immediate feedback for the proceduralist [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Performing EBUS-TBNA is preferable over surgical procedure in patients with mediastinal and hilar lymphadenopathies [20,21], and is an essential procedure to diagnose sarcoidosis [22]. The diagnostic yield of EBUSguided TBNA is as high as 86 to 91.4% in patients with pulmonary sarcoidosis [20,23]. Although Ernst et al reported the diagnostic yield of EBUS-TBNA to be 91% in patients with single hilar lymph node [24], access to hilar lymph nodes may be more difficult compared to other intrathoracic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the sample size of some of the studies was small; further studies with larger samples are needed size to confirm the diagnostic accuracy of EBUS-TBNA [13,15,16,18,19,23,34,35]. Third, most studies enrolled both malignant and benign lymphadenectasis patients, rather than specifically focusing on benign lymphadenopathy [13,17,19,23,36]. In addition, studies performed in western countries were mainly concerned with sarcoidosis, whereas those done in Asian countries focused on tuberculosis [12, 14-16, 18, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic efficiency of the various biopsy methods remains controversial. The reported diagnostic rate of cTBNA in patients with benign mediastinal LN enlargement varies between 21.4 and 76% [6][7][8][9][10][11], while that of EBUS-TBNA varies between 74.5 and 96% [12][13][14][15][16][17][18][19]. However, these studies used single-arm designs and had relatively small sample sizes.…”
Section: Introductionmentioning
confidence: 99%